Endogenous Meningococcal Endophthalmitis with Isolated Joint Involvement in Immunocompetent Adults. (19th May 2018) - Shah, Vishal; Garg, Anurag; Stanford, Miles
ABSTRACT: Purpose : We report two cases of endogenous meningococcal endophthalmitis in immunocompetent adults presenting with unilateral ocular disease and joint involvement. Methods : A retrospective review of two patients with endogenous endophthalmitis due to Neisseria meningitidis with associated arthropathy was conducted. The clinical presentation, investigations, treatment, and outcomes are presented. Results : Vitreous sampling confirmed Neisseria meningitidis via polymerase chain reaction (PCR) in both cases. PCR was positive from the knee aspirate of our second case. Both patients received topical steroids and topical, intravitreal and intravenous antibiotics. Despite this, visual outcomes were poor. Conclusions : This atypical combination of endogenous meningococcal endophthalmitis associated with meningococcal joint involvement could represent a novel pattern for the presentation of metastatic meningococcal endophthalmitis not previously described. We suggest joint aspirate PCR could be a useful adjunctive test to identify potential causative organisms in such cases where there is concurrent joint involvement in the absence of systemic features.